Implementasi Supervisi Akademik dan Manajerial Oleh Kepala Sekolah di SMK Negeri 1 Kandis - Sulaima Sulaima; Anisah Anisah; Rifma Rifma; Sufyarma Sufyarma (PAKAR Pendidikan, 2023)
This study aims to see the implementation process and the supporting factors and obstacles to implementing the Principal's Academic and Managerial Supervision at SMK Negeri 1 Kandis. The approach used is descriptive qualitative. Data collection techniques used were interviews, observation, documentation, and triangulation (combined). The data analysis techniques that researchers used were Data Reduction, Data Display, and Verification. The informants in this study were school principals, teachers, the Deputy Head of Curriculum, the Deputy Head of Student Affairs, the Deputy Head of Sarpras, the Deputy Head of Public Relations, and Hubin, Administrative Personnel. In drawing conclusions, the researcher made a comparison between the results of interviews with existing documents, then compared the results of interviews between one informant and another, whether there were differences or if there was information that was in agreement. The results of this study are: 1) the process of implementing Academic and Managerial Supervision by the Principal at SMKN 1 Kandis is going well but not optimal; 2) Supporting factors for the implementation of Academic and Managerial Supervision by the Principal at SMKN 1 Kandis are: High teacher enthusiasm for making changes, very good teacher cooperation, and most of the teachers are still young, so they are still very energetic; 3) The inhibiting factor for the implementation of Academic and Managerial Supervision by the Principal at SMKN 1 Kandis is a matter of time and the Principal's sudden assignment. With a total of 45 teachers, they must be supervised by one school principal, resulting in a long time in the supervision process.